2019
DOI: 10.1002/wer.1185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solid residence time (SRT) on functionally relevant microbial populations and performance in full‐scale enhanced biological phosphorus removal (EBPR) systems

Abstract: Investigations of the impact of solid residence time (SRT) on microbial ecology and performance of enhanced biological phosphorus removal (EBPR) process in full‐scale systems have been scarce due to the challenges in isolating and examining the SRT from other complex plant‐specific factors. This study performed a comprehensive evaluation of the influence of SRT on polyphosphate‐accumulating organisms (PAOs) and glycogen‐accumulating organisms (GAOs) dynamics and on P removal performance at Clark County Water R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Enhanced biological phosphorus removal (EBPR) has been widely applied in treating domestic wastewater, however, the application of EBPR for high-strength waste streams has hardly been explored. EBPR has been deemed as unsuitable due to the presumptions that the high-strength wastewater characteristics may not be suitable for polyphosphate accumulating organisms (PAOs), as well as concerns regarding the performance stability that are susceptible to microbial community competitions and other factors such as pH, temperature, solids retention time, influent carbon to phosphorus ratio and system configurations (Neethling et al, 2006, Onnis-Hayden et al, 2020. A limited number of studies using lab-scale EBPR reactors to treat synthetic high-strength wastewater showed promising overall P removal efficiency (~70%), but no process optimization and comprehensive evaluations of kinetics and mechanisms of the EBPR were performed in these studies (Bickers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced biological phosphorus removal (EBPR) has been widely applied in treating domestic wastewater, however, the application of EBPR for high-strength waste streams has hardly been explored. EBPR has been deemed as unsuitable due to the presumptions that the high-strength wastewater characteristics may not be suitable for polyphosphate accumulating organisms (PAOs), as well as concerns regarding the performance stability that are susceptible to microbial community competitions and other factors such as pH, temperature, solids retention time, influent carbon to phosphorus ratio and system configurations (Neethling et al, 2006, Onnis-Hayden et al, 2020. A limited number of studies using lab-scale EBPR reactors to treat synthetic high-strength wastewater showed promising overall P removal efficiency (~70%), but no process optimization and comprehensive evaluations of kinetics and mechanisms of the EBPR were performed in these studies (Bickers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research advances in fundamental understanding and successful full-scale implementation of influent carbon-independent, return activated sludge (RAS)-fermentation S2EBPR (side-stream enhanced biological phosphorus removal) process achieved concurrence of PAOs selection in presence of sludge digested centrate and promises new opportunities for its application for P-rich wastes (Onnis-Hayden et al, 2020, Wang et al, 2019). Herein, we hypothesize that the S2EBPR concept, where extended anaerobic phases to encourage hydrolysis and fermentation of sludge incorporated in the system, can be combined with short-cut N removal process to achieve simultaneous nitrogen and phosphorus removal for high strength wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that have been shown to influence the competition between PAOs and GAOs include influent C/P ratio, solid retention time (SRT), substrate type, hydraulic retention time (HRT), temperature, pH, dissolved oxygen, feeding strategy, etc. (Carvalheira, Oehmen, Carvalho, & Reis, ; Filipe, Daigger, & Grady, ; Oehmen, Vives, Lu, Yuan, & Keller, ; Oehmen, Yuan, Blackall, & Keller, ; Onnis‐Hayden et al, ; Rodrigo, Seco, PenyaRoja, & Ferrer, ; Tu & Schuler, ; Wang et al, ; Whang & Park, ).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that have been shown to influence the competition between PAOs and GAOs include influent C/P ratio, solid retention time (SRT), substrate type, hydraulic retention time (HRT), temperature, pH, dissolved oxygen, feeding strategy, etc. (Carvalheira, Oehmen, Carvalho, & Reis, 2014;Filipe, Daigger, & Grady, 2001;Oehmen, Vives, Lu, Yuan, & Keller, 2005a;Oehmen, Yuan, Blackall, & Keller, 2005b;Onnis-Hayden et al, 2019;Rodrigo, Seco, PenyaRoja, & Ferrer, 1996;Tu & Schuler, 2013;Wang et al, 2006;Whang & Park, 2006). Evaluation of full-scale EBPR performance data reported by Gu et al (2008) indicated that process stability was positively correlated with the influent C/P ratio (as bCOD or BOD/P) and they hypothesized that although excessive available carbon can promote the proliferation of GAOs, stable process performance can be maintained as long as the operational conditions are controlled to kinetically favor the growth of PAOs over GAOs.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, each sludge sample was independently performed a phosphorus release and uptake kinetics batch test as described by Gu et al (2008) . Raman-based phenotypic survey was performed on the sludge extracted throughout the batch test following the preparing and acquisition protocol described by Majed et al (2008) and Onnis-Hayden et al (2019). All spectra were acquired with a 400–1800 cm –1 range, which is often referred as the “fingerprint range” for various cellular or biomass substances. ,, All acquired spectra were then preprocessed with LabSpec 6 (HORIBA, 2 Miyanohigashi, Kisshoin, Minamiku Kyoto 601-8510 Japan), for cosmic spike removal, smoothing, background subtraction, baseline correction and -normalization. The survey resulted in a total of 922 spectra from eight WRRF-specific data sets labeled from A to H, with F and H had larger sample size (>200) in comparison to the rest six (80–89).…”
Section: Methodsmentioning
confidence: 99%